Tubal Ectopic Pregnancy after 11 Years of Bilateral Tubal Ligation (Northern International Medical College Journal, 2015)
Tubal ligation is a well excepted method of contraception. Permanent contraception by tubal ligation is one of the most commonly used contraceptive methods in United States, also most popular form of contraception worldwide. Although pregnancy after ligation is uncommon, it can occur and may be ectopic. Surprisingly, failures are not limited to the first year or two but continued to appear even after many years during follow up. In this paper we report a case of ectopic pregnancy in a patient who underwent bilateral tubal ligation11years ago during caesarean delivery for contraception.Northern International Medical College Journal Vol.7(1) Jul 2015: 119-120